Study of fame production from waste cooking oil: Operation in batch and continuous regime with regeneration of enzyme catalyst. (February 2020) - Sorte, S.; Ribeiro, J.P.; Coutinho, J.A.P.; Nunes, M.I.
Abstract: This work aimed to: (i) assess the performance of Novozyme® 435 for FAME production from waste cooking oil (WCO) under different oil acid values and enzyme-to-oil ratios; (ii) test different regeneration methods and assess the regenerated enzyme's performance; and (iii) determine FAME yield in continuous operation regime. Oil acid values up to 104 mg KOH.g −1 and enzyme-to-WCO ratios of up to 20:80 (% wt.) were studied, with maximum yield recorded for increasing acid values and enzyme-to-WCO ratio. FAME production from WCO yield ranging 50%–80% was recorded for 5 consecutive production cycles (8h each, in batch regime) with no regeneration of the enzyme. Among the enzyme regeneration methods tested, the highest FAME yield was recorded using t-butanol washing followed by enzyme incubation in the WCO before reusing it. Operation in continuous regime, including enzyme regeneration, produced the highest FAME yield (maximum of 86 %). Thus, effectiveness of the regenerating process and efficiency of continuous production of FAME from WCO (up to 576h) were observed.